Insulinoma in a patient with HIV infection on antiretroviral treatment - Paz-Ibarra, José Luis (2020)
We present the case of a 43-year-old patient with a diagnosis of HIV infection on antiviral treatment who developed seizures without response to anticonvulsant treatment. The metabolic and structural study showed the presence of hyperinsulinemic hypoglycemia whose evaluation concluded that she had an insulinoma and was therefore subjected to subtotal pancreatectomy without recurrence of seizure episodes during the follow-up.